The role of modified teeth in the function of prolonged bites in Hierophis viridiflavus (Serpentes: Colubridae) - Paterna, Alessandro (Phyllomedusa: Journal of Herpetology, 2023)
Analysis of the maxillary, palatine, pterygoid, and dentary bones of the Western Whipsnake, Hierophis viridiflavus carbonarius, revealed the presenceof grooves and ridges in the teeth on the four dentiferous bones. Enlarged and modified rear teeth were found on the posterior maxillaries, separated by alveolar diastema and aligned differently from the anterior maxillary teeth. In both live and dissected specimens, Duvernoy’s gland, associated with the production of toxins, surrounds the rear maxillary teeth, which deliver the secretions produced by the gland. These characters, plus theinfliction of prolonged bites, facilitate the subduing of prey. The morphology of the palatomaxillary arch places H. viridiflavus in the group of opisthoglyphous colubroids, whose modified fangs facilitate the inoculation of secretions, considered a “primitive form of venom.” Other species of large sympatric colubroids were also examined, and some analogous structures were observed.